Age estimation equations using vertebral osteophyte formation in a Thai population: Comparison and modified osteophyte scoring method - Sithee Praneatpolgrang (2019)
© 2019 Anatomy & Cell Biology. Age estimation from skeletal remains is an important step in forensic biological identification. The main objective of this study is to develop an age estimation equation for the Thai population from vertebral osteophytes. Each vertebra in the cervical, thoracic and lumbar segments was scored for degree of osteophyte formation. Classification was carried out in accordance with the criteria established by Snodgrass and Watanabe, and used a new modified score of the length of vertebral osteophyte for age estimation. The sample included 400 individuals (262 males, 138 females) ranging in age from 22 to 97 years. A sample of Thai vertebral columns was used, the columns being divided into the following groups of vertebrae: cervical (C2-C7), thoracic (T1-T12), and lumbar (L1-L5). Each vertebra was scored for the degree of osteophyte formation and the accumulated data was analyzed statistically. Correlation coefficients and R-squared from mean in lumbar vertebrae for females of criteria established by the method of Snodgrass and Watanabe, the new modified score by length of vertebral osteophytes were 0.801 and 0.642 (P<0.01); 0.755 and 0.57 (P<0.01); 0.786 and 0.618 (P<0.01), respectively. This study presents all 23 subcategories (C2-L5) of the vertebrae to apply in real situations, showing all age estimation equations for males, females and combined sexes of unknown sex. One application of this study is age estimation when dealing with forensic cases in the Thai population.